Research on Innovative Freshwater Generation Through Hygroscopic Solar Chimney - Imran Basri Shamih; Alimin, Ahmad Jais (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This study focuses on the design of a novel freshwater generating system using a hygroscopic solar chimney. The system will use solar chimney and desiccant dehumidification methods to capture water vapor from the surrounding air and create freshwater. The study looks at the operation characteristics of the liquid desiccant system, such as air flow rate, desiccant solution, humidity, and regeneration. Meteorological data from the Gaza region are used to assess the system's performance. Calculations are performed to estimate water vapor partial pressure, air volume, and mass of dry air, mass of water vapor, specific humidity, moisture content, and moisture absorption. The results show that the suggested system may generate freshwater from ambient air in arid and semi-arid environments, contributing to a sustainable water supply.